The Influence of Gender Differences in Mathematics Anxiety on Mathematics Performance - Asomah, Richard Kyere; Magurd Kwabena , Joshua; Assamah, Gabriel; Narh-Kert, millicent; Nusrat Manu, Harriette (International Journal of Educational Innovation and Research, 2025)
Mathematics anxiety is a recurrent issue that has profound effect on students, particularly females. This study is aimed at exploring the effect of gender differences in mathematics anxiety on mathematics performance among students in some selected Senior High Schools (SHS) in Ghana. A cross-sectional survey was employed as the research design for the study. A total of 370 SHS students (185 males and 185 females) were sampled through Stratified sampling technique. An Abbreviated Mathematics Anxiety rating scale (AMAS) and Mathematics Achievement Test (MAT) were adapted to measure student’s anxiety levels and mathematics performance respectively. Means and standard deviations, percentages, independent sample t-test and Pearson correlation coefficient were employed in the data analysis. The results showed a notable gender-based variations (high, moderate and low) with both males and females exhibiting high prevalence of moderate levels in mathematics anxiety. Further, the study found disparities in the performance of the students in the MAT conducted with male students exhibiting a higher level of performance in comparison with the female counterparts. Finally, a moderate negative relationship between students' mathematics anxiety level and their mathematics performance was found. Thus, the higher the levels of mathematics anxiety, the lower the mathematics performance and vice versa. Therefore, efforts to reduce mathematics anxiety should be directed towards both males and females, with specific attention given to addressing the unique experiences of female. Implications for practice, policy and further research are discussed.